First Dorsal Metacarpal Artery Flap : A Reliable Option for Reconstruction of Extensive Pulp Defects of the Thumb - Chowdhury, Maruf Alam; Khan, Mohammad Saneat Jahan; Sarker, Avijit; Hossain, Mohammad Abul (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: Thumb pulp defects are commonly due to avulsion injuries. The choice of reconstructive procedure for thumb depends on the amount and type of tissue lost. The First Dorsal Metacarpal Artery (FDMA) flap is a versatile method with minimum donor site morbidity which provides protective sensation, adequate length, stability and good mobility. Method: This study was done over a period of 2 years and involved 15 consecutive cases of thumb pulp defects treated at our institution. The patient included 13 men and 2 women ranging in age from 16 to 60 years. The defects were ranged from 2cm x 1.5cm to 5cm x 3cm. Results: All flaps survived completely except one had marginal flap necrosis healed without the need for a secondary procedure. Donor site was covered with full thickness skin graft that healed spontaneously. Conclusion: First dorsal metacarpal artery flap offers a sensate, pliable and versatile coverage for soft tissue defects of the thumb. It provides good functional Results with minimum donor site morbidity. J Bangladesh Coll Phys Surg 2023; 41: 53-57